Unilateral Erythema Nodosum following Norethindrone Acetate, Ethinyl Estradiol, and Ferrous Fumarate Combination Therapy - Michelle S. Min; Rob Fischer; John B. Fournier (Case Reports in Obstetrics and Gynecology)
Erythema nodosum is a septal panniculitis that typically presents as symmetric, tender nodules on the anterior aspects of bilateral lower extremities. Nearly half of cases are due to secondary causes, with oral contraceptive pills being the leading pharmaceutical cause. However, to our knowledge, there has yet to be a published association with norethindrone acetate, ethinyl estradiol, and ferrous fumarate. We report our experience with a 30-year-old woman who developed unilateral tender nodules within a month of starting 1 mg norethindrone acetate and 20 mcg ethinyl estradiol daily. Of note, she had previously taken oral contraceptives with the same estrogen agent but different progesterone, without problems. We conclude that systemically triggered erythema nodosum can present with lesions localized to one extremity. When a patient presents with tender, firm nodules, clinicians should consider the possibility of erythema nodosum and its triggers, such as oral contraceptives. Additionally, should a patient on hormonal therapy develop erythema nodosum, changing the progesterone agent may allow the patient to continue similar therapy without developing symptoms.